Spatio-temporal patterns and risk factors of foot-and-mouth disease in Malawi between 1957 and 2019 - Chimera, E.T.; Fosgate, G.T.; Etter, E.M.C.; Temesgen, Wudu; Kamwendo, G.; Njoka, P. (Elsevier, 2022)
Foot-and-mouth disease (FMD) is an important livestock disease causing short-term and long-term production losses and hindering local and international trade. To gain access to lucrative foreign markets and also improve local trade, there is a need to employ effective preventive and control strategies. Although FMD has been present in Malawi for over 60 years, little knowledge is available concerning the dynamics and drivers of FMD in the country. A modelling study based on retrospective data was conducted to establish the spatio-temporal distribution and determine the risk factors associated with FMD in Malawi. A retrospective space-time analysis was performed and a matched case-control study was carried out to investigate risk factors. The number of reported FMD outbreaks has descriptively increased after 2000 and the disease has spread to previously unaffected areas. Two significant spatio-temporal clusters of FMD were identified; one in the southern region and the other in the northern region. An analysis of only index cases (first detected locations) also detected two clusters with one in the northern region and the other in the southern region. Higher beef cattle density (p = 0.023), higher pig density (p = 0.043) and increased distance to wildlife protected areas (p = 0.036) were positively associated with the risk of FMD while increased distances to international borders (p = 0.008) and roads (p = 0.034) were associated with reduced risk of FMD. High FMD risk areas were observed in the southern and northern regions but not in the central region during the early years (1957–1981). The more recent increase in FMD risk at the end of the study period (2019) in the central region might be attributed to increases in livestock density in this region. These findings provide insight into the pattern of FMD occurrence that will promote informed decisions for the progressive control of FMD in the region.